Novel verdicts of nifedipine encapsulated with cyclodextrin in new-fangled form of microsponges - Thakur, Suchi; Jain, NIlesh; Jain, Deepti; Jain, Surendra Kumar (Journal of Drug Delivery and Therapeutics, 2019)
The fundamental approach for the microsponge technologies arises in solid dosage forms because they showing a promising technology for nifedipine drug in hypertension control. As nifedipine drug is chosen due to its hydrophobic nature second short half-life, third low remark in plasma concentration. Cyclodextrin-based microsponges with different polymer are novel finding in the microsphere technology, the crosslinking of polymers blends with respect to cyclodextrin will enhance the entrapment of nifedipine drug in the new-fangled form by emulsification solvent method and futher Lyophilization. The different microsponges batches are formulated the optimize batch was MN3 with angle of repose; 21.80 ± 0.63., Hausner ratio 1.132, Carrs index 0.132 and higher % drug content (80.5 ± 0.97 %). showed 99.41 ± 1.05 % drug release during 36 hr in vitro release . After that the stability data disclose superior drug retention of loaded nifedipine, besides consistent in vitro release pattern over a period of 90 days. Keywords: Microsponges, Cyclodextrin, Polymers, Nifedipine